2016
DOI: 10.4103/1735-3327.192304
|View full text |Cite
|
Sign up to set email alerts
|

A histologic, histomorphometric, and radiographic comparison between two complexes of CenoBoen/CenoMembrane and Bio-Oss/Bio-Gide in lateral ridge augmentation: A clinical trial

Abstract: Background:Several grafting materials have been used for alveolar ridge augmentation. The literature lacks researches to compare CenoBone to other grafting materials. The aim of this study was to compare CenoBone/CenoMembrane complex to Bio-Oss/Bio-Gide complex in lateral alveolar bone augmentation in terms of radiographic, histologic, and histomorphometric parameters.Materials and Methods:In this randomized controlled trial, ten patients who needed lateral ridge augmentation were selected and augmentations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…According to the literature on human studies using this form of xenograft six months after augmentation, an older study by Zitzmann et al in 2001 [ 77 ] confirmed 36.7 ± 26.6% newly formed bone, 30.5 ± 4.6% residual BSB, and 37.6 ± 20.5% soft tissue structures, which is similar to the results obtained in this study. A more recent study by Amoian et al [ 78 ] can also be related to this control group in terms of newly formed bone, which was 38.66% in this study, although the sample consisted of only six patients. On the other hand, the study by Scarano et al [ 79 ], although performed on a much larger number of subjects, confirmed the regenerative effect of Bio-Oss ® in terms of newly formed bone with 39 ± 1.6%, 31 ± 1.4%, residual BSB, and 34 ± 1.6% soft tissue structures, which is the closest to the results obtained in this study six months after augmentation with the same BSB.…”
Section: Discussionmentioning
confidence: 65%
“…According to the literature on human studies using this form of xenograft six months after augmentation, an older study by Zitzmann et al in 2001 [ 77 ] confirmed 36.7 ± 26.6% newly formed bone, 30.5 ± 4.6% residual BSB, and 37.6 ± 20.5% soft tissue structures, which is similar to the results obtained in this study. A more recent study by Amoian et al [ 78 ] can also be related to this control group in terms of newly formed bone, which was 38.66% in this study, although the sample consisted of only six patients. On the other hand, the study by Scarano et al [ 79 ], although performed on a much larger number of subjects, confirmed the regenerative effect of Bio-Oss ® in terms of newly formed bone with 39 ± 1.6%, 31 ± 1.4%, residual BSB, and 34 ± 1.6% soft tissue structures, which is the closest to the results obtained in this study six months after augmentation with the same BSB.…”
Section: Discussionmentioning
confidence: 65%
“…Autogenous and allogenic bone substitutes and even autogenous block grafts have been used for horizontal ridge augmentation in clinical studies ( Starch-Jensen et al, 2022 ). However, granular graft materials have been used for horizontal ridge augmentation in the majority of GBR-based procedures ( Amoian et al, 2016 ). Nonetheless, clinical information regarding the 1:1 ratio of autogenous bone/xenograft material or even autogenous bone/synthetic material is much more abundant than other graft materials ( Elamrousy et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bio-Gide® is a porcine resorbable membrane, comprised of a double layer of Type I and III collagen, indicated for tissue regeneration. It may act as a tissular barrier as it promotes the deposition of new bone with a stable absorption rate, without causing tissue inflammation 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…With the aim of enhancing GBR (Guided Bone Regeneration), different biomaterials associated with the use of membranes have been studied 13 , 14 , 16 . Thus, being a synthetic hormone that could potentially impact on bone formation, melatonin could be associated with membranes in regeneration processes.…”
Section: Introductionmentioning
confidence: 99%